Ultrastructural study of the duck brain infected with duck Tembusu virus - Yang, Sheng; Shi, Yonghong; Wu, Jingxian; Chen, Qiusheng (Frontiers in Microbiology, 2023)
Duck Tembusu virus (DTMUV) is an emerging avian flavivirus characterized by causing severe ovaritis and neurological symptoms in ducks. The pathology of the central nervous system (CNS) caused by DTMUV is rarely studied. This study aimed to systematically investigate the ultrastructural pathology of the CNS of ducklings and adult ducks infected with DTMUV via transmission electron microscopy technology at a cytopathological level. The results showed that DTMUV caused extensive lesions in the brain parenchyma of ducklings and slight damage in adult ducks. The neuron was the target cell of DTMUV, and virions were mainly observed in their cisternae of rough endoplasmic reticulum and the saccules of Golgi apparatus. The neuron perikaryon showed degenerative changes where the membranous organelles gradually decomposed and disappeared with DTMUV infection. Besides neurons, DTMUV infection induced marked swelling in astrocytic foot processes in ducklings and evident myelin lesions in ducklings and adult ducks. The activated microglia were observed phagocytizing injured neurons, neuroglia cells, nerve fibers, and capillaries after the DTMUV infection. Affected brain microvascular endothelial cells were surrounded by edema and had increased pinocytotic vesicles and cytoplasmic lesions. In conclusion, the above results systematically describe the subcellular morphological changes of the CNS after DTMUV infection, providing an ultrastructural pathological research basis for DTMUV-induced neuropathy.